Penyakit Kerupuk Tembakau di Sumatera Barat - Jumsu Trisno; Rahil Ade Rifqah; Martinius Martinius (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Tobacco leaf curl disease (“kerupuk”) is a new disease on tobacco in West Sumatra. This disease has spread throughout the tobacco planting area in District Limapuluh Kota with intensity of 2.5–26.3%. DNA fragment of 1600 bp was successfully amplified using polymerase chain reaction method with primer pairs for Begomovirus PAL1v 1978/PAR1c 715 from tobacco leaves showing symptoms. This result indicated Begomovirus infection. Sequence analysis based on NCBI BLAST program showed that Begomovirus infecting tobacco in West Sumatera has the highest homology of 89% and 91–97% with Pepper yellow leaf curl Indonesia Virus infecting tomato and chili pepper in West Sumatera, respectively. This is considered as the first report of Begomovirus infection on tobacco in West Sumatra.